The Importance of Maslahah Orientation in Sharia Institutions - Edastama, Primasatria (Pandawan, 2021)
This research aims to look at the importance of a Sharia Institution in orienting its institutions on an orientation based on benefit. This research is based on the lack of attention of some Sharia Institutions on the principle of the basic purpose of Sharia that is to be able to achieve benefit. In this study will be seen the influence of benefit on satisfaction and loyalty to the Sharia Institution in. This research will use structural equation model method as data processing technique. Data is collected using quiestionaire distributed to sharia institutions customers. This research found that orientation in maslahah is a very important factor in building loyalty to Sharia Institutions. In addition, the orientation on the maslahah needs to be improved as a means in improving customer satisfaction. The results of this study are expected to be the basis for sharia institutions to focus more on the orientation of maslahah for their institutions in accordance with the basic principles of Sharia itself